2018
DOI: 10.1139/cjce-2017-0058
|View full text |Cite
|
Sign up to set email alerts
|

Rheological characterization of asphalt binders treated with bio sealants for pavement preservation

Abstract: Pavement preservation is playing an increasingly significant role in 1 maintaining our aged pavement infrastructure under severe budget constraints. One 2 important component is the use of surface treatments based on application of sealants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
1
3
0
Order By: Relevance
“…Other important parameter is the tan, obtained by the ratio of G" and G'. As displayed in Figure 3, the tan  values were < 1 until the c, confirming the elastic behavior for the P. pubescens NE (Syahariza & Yong, 2017;Ghosh et al, 2018).…”
Section: Oscillatory Rheological Measurementssupporting
confidence: 72%
“…Other important parameter is the tan, obtained by the ratio of G" and G'. As displayed in Figure 3, the tan  values were < 1 until the c, confirming the elastic behavior for the P. pubescens NE (Syahariza & Yong, 2017;Ghosh et al, 2018).…”
Section: Oscillatory Rheological Measurementssupporting
confidence: 72%
“…Also, the rejuvenating ability of emulsion type additives is well known in which emulsion rejuvenators can affect the change in stiffness of the aged AB sufficiently (81,82). However, a comparative study showed that the restoring impact of these, such as the polymerized maltene-based emulsion composed of petroleum resin oil base, is lower than organic rejuvenators (83) or even the same (84).…”
Section: Petroleum Type Rejuvenatorsmentioning
confidence: 99%
“…There are plenty of studies about the effect of rejuvenators on binder rheology. Rejuvenators soften the aged bitumen causing the increase of penetration, ductility, phase angle and colloidal instability index, and decrease of viscosity and complex modulus [3,4,[12][13][14][15][16][17][18]. Meanwhile, recent investigations have shown a close relationship of microstructure with chemical composition and rheological properties of bitumen [19][20][21][22][23], assisting on understanding the rejuvenation mechanism.…”
Section: Introductionmentioning
confidence: 99%